Improving the Quality of Financial Reports through Human Resources, Information Technology, Internal Controls, the Implementation of Government Accounting Standards, and Leadership Style: (Case Study on Regional Apparatus Organization of West Papua Province) - Syarifuddin Syarifuddin; Marlina Malino; Stevanie Lusye Sahertian; Muhammad Arif Wiratama Fattah; Christine S.M. Marpaung; Yubelina Mamoribo (Advances in Economics & Financial Studies, 2026)
Purpose: This study investigates the influence of human resource competency, information technology utilization, internal control systems, Government Accounting Standards implementation, and leadership style on the quality of financial reporting in Regional Apparatus Organizations of West Papua Province. Research Method: This study employed a quantitative descriptive design using primary data collected through structured questionnaires. Responses were measured using a five-point Likert scale ranging from strongly disagree to agree strongly. The data were converted into numerical values and analyzed using multiple linear regression to examine the relationships between the independent variables and financial reporting quality. Results and Discussion: The study involved 46 Regional Apparatus Organizations, with a total population of 184 respondents. The findings indicate that human resource competency, internal control systems, and Government Accounting Standards implementation positively affect financial reporting quality. However, information technology utilization and leadership style do not significantly affect the quality of financial reporting in West Papua Province. Implications: These findings provide empirical insights for policymakers and government institutions, particularly Regional Apparatus Organizations, in evaluating and improving government financial reporting quality. Originality: This study enriches the literature by providing empirical evidence regarding factors influencing government financial reporting quality in West Papua Province.